The effectiveness of a proposed strategy based on the Pomodoro technique in developing historical comprehension skills among fourth-grade literary female students in the subject of history (Journal of Human Sciences, 2025)
The objective of the current research is to learn the effectiveness of a proposed strategy based on the Pomodoro technique (Pomodoro) In developing the historical understanding skills of the fourth graders in history, in order to achieve the research objective, the researcher adopted the semi-experimental research curriculum, using the experimental design of two equal groups with a post-post test of historical understanding skills, the experiment was applied to a sample of female students reached (74) Students, Experimental Group (37) and Control Group (37) Students of Fourth Grade Literary at Rafidain Girls' High School for the first semester of the academic year (2024-2025) The two groups were rewarded with several variables (previous knowledge, time age calculated by months) Thus, the research experiment's requirements of (Article identification, formulation of general and special objectives, preparation of teaching plans), In addition, the research tool was built a historical understanding test consisting of (30) Thematic paragraph (multiple choice) spread over (3) historical understanding skills (Translation, interpretation, conclusion) Where the veracity and consistency of the test was verified using appropriate statistical means, the pilot group was taught in the proposed strategy and control group in the traditional manner of the subject school itself and in agreement with the researcher